2014
DOI: 10.1111/exd.12551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anti‐TNFα agents on circulating endothelial‐derived and platelet‐derived microparticles in psoriasis

Abstract: Psoriasis involves TNF-a secretion leading to release of microparticles into the bloodstream. We investigated the effect of TNF blockers on microparticles levels before and after treatment in patients (twenty treated by anti-TNF-a agents and 6 by methotrexate) with severe psoriasis. Plasmatic microparticles were labelled using fluorescent monoclonal antibodies and were analysed using cytometry. Three months later, 70% of patients treated with anti-TNF-a agents achieved a reduction in PASI score of at least 75%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
14
0
4
Order By: Relevance
“…TNF-α has been shown to be a potent stimulator of MVs in vitro, including from cardiomyocytes [58,59,[66][67][68] and it is correlated with MV levels in the circulation [22]. In patients with psoriasis, treatment with anti-TNF-α, a commonly used therapy in autoimmune conditions, led to a decrease of platelet and endothelial-cell-derived MVs following 3 months of treatment [69]. This finding supports findings from Sari et al [70] who showed that platelet and endothelial MVs were significantly reduced in an ankylosing spondylitis patient receiving anti-TNF-α therapy, compared with conventional therapy.…”
Section: Inflammationmentioning
confidence: 99%
“…TNF-α has been shown to be a potent stimulator of MVs in vitro, including from cardiomyocytes [58,59,[66][67][68] and it is correlated with MV levels in the circulation [22]. In patients with psoriasis, treatment with anti-TNF-α, a commonly used therapy in autoimmune conditions, led to a decrease of platelet and endothelial-cell-derived MVs following 3 months of treatment [69]. This finding supports findings from Sari et al [70] who showed that platelet and endothelial MVs were significantly reduced in an ankylosing spondylitis patient receiving anti-TNF-α therapy, compared with conventional therapy.…”
Section: Inflammationmentioning
confidence: 99%
“…Dans différentes pathologies, l'origine et le nombre des MP circulantes sont significativement modifiés, d'où leur intérêt en tant que biomarqueur. C'est le cas pour les MP dérivées des cellules endothéliales (EMP) dont la concentration sanguine est plus éle-vée que la normale dans le psoriasis [4] et qui activent les PDC [5] (➜). À l'inverse, les MP dérivées de plaquettes (PMP) diminuent la réponse inflammatoire des PDC [5,6].…”
Section: Cellules Dendritiques Plasmocytoïdes Microparticules Et Patunclassified
“…Deux principales stratégies sont envisageables : diminuer/modifier la génération des MP ou augmenter leur élimination de l'organisme. La première approche est utilisée chez des patients souffrant de psoriasis par la neutralisation du TNF- (un puissant inducteur de la production des EMP) résultant en une diminution significative du nombre des EMP circulantes et en un bénéfice clinique [4]. Le potentiel de la seconde approche est illustré par la régression du syndrome lupique ou de l'inflammation intestinale dans des modèles murins, suite à l'augmentation de la clairance de vésicules exposant les PtdSer (corps apoptotiques) par la surexpression des récepteurs des PtdSer (PtdSerR), Mertk (mer tyrosine kinase) ou BAI-1 (brainspecific angiogenesis inhibitor-1) [7,8].…”
Section: Cellules Dendritiques Plasmocytoïdes Microparticules Et Patunclassified
See 2 more Smart Citations